Praisesong: One (Worn) Path through AEPL - Libby F Jones (Journal of the Assembly for Expanded Perspectives on Learning, 2015)
A longtime member takes a poetic look at AEPL's history, philosophy, activities, and her ongoing participatory role in the organization.